The Consequences of Heavy Metals Resulting from Terrorist Operations in Three Regions of Baghdad, Iraq on Thyroid Function - Kadhim, Sara J; Jawad, Alaa H; Saifullah, Perry H (Al-Nahrain Journal of Science, 2018)
The heavy metals mercury (Hg), lead (Pb) and cadmium (Cd) are widely known of being toxicants. exposure to a variety of dangerous toxic effects has been attached in all humans.in this paper the effect of terrorist operation on thyroid gland functions in a sample of Iraqi individual (Al-karradah and Abo-Gharib) comparison with Al-jadria rejoin as (control). the correlation between sera thyroid hormones thyroxine T4, triiodothyronine T3, Thyrotropin TSH and Thyroglobulin-Ab (Tg-Ab) and the levels-of lead, cadmium, also mercury have-been measured. 75 volunteers from three Iraqi areas were included in this study‎. our examination proposes an inverse relationship between Hg presentation and thyroid hormones, a positive ‎correlation between Cd exposure and thyroid hormones‎, but the associations with Pb was negative. there were significant positive correlations between the heavy metals themselves. In this manner, increased heavy metals exposure might be a factor in the etiology of hypothyroidism diseases ‎and thyroid gland function. the result of this study showed that the effect of heavy metals (blood serum Hg, blood serum Pb, blood serum Cd) on thyroid hormones, and the effect of military and terrorist operations on the thyroid gland. In the end we concluded that the heavy elements resulting from the explosions and terrorist operations in the area of (Al-karadah, Abo-Gharib) high compared with the control (Al-jadria), this leads to many diseases on the health of the human body and also the effect of heavy elements on the thyroid gland and its negative effect on thyroid hormones and cause thyroid disease